Electrochemical Deposition (ECD) of ZnO as the Photoanode in Dual-Chamber Photocatalytic Fuel Cell (PFC) for Methyl Red Degradation - Antonio Choon Kiat, Niang; Liu, Jia Chee; Tay, Meng Guan (Wiley-VCH GmbH, 2023)
Photocatalytic fuel cell (PFC) is known to treat the organic-based wastewater efficiently. The coating method of zinc(II) oxide (ZnO) as the photocatalyst on the zinc (Zn) plate of photoanode plays important role in maintaining the efficiency and power generation from PFC. In the present study, a new coating method of ZnO on the zinc plate is developed by using electrochemical deposition (ECD) and the removal efficiency as well as power generation are compared with typical ultrasonicate method. A dual-chamber PFC is constructed with ZnO/Zn photoanode and graphite plate as the cathode to treat methyl red dye synthetic wastewater. The surface morphology of both coating methods of ZnO/Zn photoanode is observed using scanning electron microscope (SEM) before and after the treatments. The dual chamber PFC with ECD coating shows a faster complete degradation rate with higher power generation than ultrasonicate method. Although, both coating methods can reach to 100% degradation efficiency of methyl red dye, the maximum power output for ultrasonicate method is 134.67 mW cm−2 while for ECD is 285.30 mW cm−2 under optimum conditions.